SPE Eastern Regional Meeting 2015
DOI: 10.2118/177304-ms
|View full text |Cite
|
Sign up to set email alerts
|

Water-Rock Interaction for Eagle Ford, Marcellus, Green River, and Barnett Shale Samples

Abstract: Knowledge of water-rock interactions on the surface of fractures is important to develop an understanding of the geological structures and changes within the formation, to determine the water pollutants in produced water during hydraulic fracturing, and to manage effectively the produced waters. To obtain this knowledge, the water-shale interaction is investigated on carbonate-rich (Eagle Ford), organic-rich (Green River), clay-rich (Barnett), and other minerals rich (Marcellus) shale samples.Crushed shale sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Mineral compositions of shale reservoirs can vary significantly from carbonate-rich to silica-rich resulting in a wide variation of the pore size, porosity, permeability, and mechanical strength. ,,,,,− …”
Section: Shale Petrophysics and Geochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Mineral compositions of shale reservoirs can vary significantly from carbonate-rich to silica-rich resulting in a wide variation of the pore size, porosity, permeability, and mechanical strength. ,,,,,− …”
Section: Shale Petrophysics and Geochemistrymentioning
confidence: 99%
“…However, at high ionic strengths (such as those observed in produced water), the ability for water to solvate ions becomes limited; the counterion effect can also be significant. Ali and Hascakir exposed crushed samples of Eagle Ford and Barnett shales to deionized water. The former has a higher proportion of gypsum compared to the latter but the results showed that the sulfate concentration in the two shales was similar.…”
Section: Evolution Of Shale Flow Channels Due To Reactive Transportmentioning
confidence: 99%
“…Second, dissolution of the calcite in water results in an increase in calcium concentration which will adsorb to the DDL and therefore less water is needed to compensate for the negative charge of the clay in DDL. a.Data from Zhang et al (2015) b.Data from Ali and Hascakir (2015) SPE-180372-MS…”
Section: Investigation Of Clay Swelling Mechanismsmentioning
confidence: 99%